Cryogenically preserved RBCs support gametocytogenesis of Plasmodium falciparum in vitro and gametogenesis in mosquitoes - Ashutosh K. Pathak; Justine C. Shiau; Matthew B. Thomas; Courtney C. Murdock (Malaria Journal, 2018)
Abstract Background The malaria Eradication Research Agenda (malERA) has identified human-to-mosquito transmission of Plasmodium falciparum as a major target for eradication. The cornerstone for identifying and evaluating transmission in the laboratory is standard membrane feeding assays (SMFAs) where mature gametocytes of P. falciparum generated in vitro are offered to mosquitoes as part of a blood-meal. However, propagation of “infectious” gametocytes requires 10–12 days with considerable physico-chemical demands imposed on host RBCs and thus, “fresh” RBCs that are ≤ 1-week old post-collection are generally recommended. However, in addition to the costs, physico-chemical characteristics unique to RBC donors may confound reproducibility and interpretation of SMFAs. Cryogenic storage of RBCs (“cryo-preserved RBCs”) is accepted by European and US FDAs as an alternative to refrigeration (4 °C) for preserving RBC “quality” and while cryo-preserved RBCs have been used for in vitro cultures of other Plasmodia and the asexual stages of P. falciparum, none of the studies required RBCs to support parasite development for > 4 days. Results Using the standard laboratory strain, P. falciparum NF54, 11 SMFAs were performed with RBCs from four separate donors to demonstrate that RBCs cryo-preserved in the gaseous phase of liquid nitrogen (− 196 °C) supported gametocytogenesis in vitro and subsequent gametogenesis in Anopheles stephensi mosquitoes. Overall levels of sporogony in the mosquito, as measured by oocyst and sporozoite prevalence, as well as oocyst burden, from each of the four donors thawed after varying intervals of cryopreservation (1, 4, 8, and 12 weeks) were comparable to using ≤ 1-week old refrigerated RBCs. Lastly, the potential for cryo-preserved RBCs to serve as a suitable alternative substrate is demonstrated for a Cambodian isolate of P. falciparum across two independent SMFAs. Conclusions Basic guidelines are presented for integrating cryo-preserved RBCs into an existing laboratory/insectary framework ...